Development and Climate Change : A Strategic Framework for the World Bank Group - World Bank (Washington, DC, 2013)
The framework provided a road map for climate action for the World Bank Group (WBG) over fiscal years 2009-11, setting out the WBG's objectives, principles, areas of focus, and major initiatives in the field of climate change. The framework was organized around six action areas: 1) supporting climate actions in country-led development processes; 2) mobilizing additional concessional and innovative finance; 3) facilitating the development of market-based financing mechanisms; 4) leveraging private sector resources; 5) supporting accelerated development and deployment of new technologies; and 6) stepping up policy research, knowledge, and capacity building. Climate change is one of the multiple stressors that affect the environment and impact on income and welfare. Further, its impact is worsened by other environmental damages. Looking ahead, strategies to combat climate change have to account for the continued need for rapid growth in developing countries. In this context, the World Bank is now looking at climate change in a holistic manner, bringing together climate change efforts with work on growth and broader management of natural resources and pollution. The WBG has successfully worked with clients and partners to mainstream climate considerations into the WBG's core business and strategies to reach impact on the ground. Yet this remains a make-or-break decade for climate action despite escalating levels of engagement within and outside the WBG.